Adaptabilidade e estabilidade de híbridos comerciais de milho na região Centro-Sul do Paraná na safra 2008/2009 - Pfann, Alessandra Zawadzki (2010)
This research aimed to estimate adaptability and stability of 35 commercial maize hybrids, recommended for five environments in South-Center region of Paraná state, and to compare five statistical methods for genotype x environment interaction analysis. As the grain yield data were available, the methodologies by Annicchiarico (1992), Eberhart & Russell (1966), Lin & Binns (1988) modified by Carneiro (1998), centroids by Rocha et al.(2005) and modified by Nascimento et al. (2009) and AMMI. The trials were carried out in randomized blocks design, in three replications. The mean grain yield varied from 3.579,69 kg ha?¹ to 11.128,46 kg ha?¹, and the total average was 7.998,07 kg ha?¹. The methods by Annicchiarico (1992), Lin & Binns (1988) modified by Carneiro (1998), centroids by Rocha et al.(2005) and modified by Nascimento et al. (2009) were highly correlated. However, one of these methodologies can be used along with Eberhart & Russell`s (1966) and improve information about stability analysis. AMMI analysis had low association to other methodologies, and should be considered as complementary to other methodologies. In the majority of methodologies, the hybrids 30F36, AS1579, AG8021 and 30B39 presented high general adaptability, and 30F35 was the most productive. 30K64 was the most adapted for unpropitious environment, and so were AG8021 and 2B707. DKB234 had the lower adaptability.